Production and nutritive value of piatã grass and hybrid sorghum at different cutting ages - Andréia da Cruz Quintino (Acta Scientiarum. Animal Sciences, 2013)
The influence of cutting age on production and nutritive value of piatã grass (Brachiaria brizantha cv. BRS Piatã) and hybrid sorghum (Sorghum spp. cv. BRS 801) under an integrated crop- livestock system was evaluated. The trial was carried out at the Embrapa Beef Cattle (2027 S; 5437 W) in Campo Grande, Mato Grosso do Sul State, Brazil, between April and October 2009. Experimental design consisted of randomized blocks with four replicates. Treatments were distributed across a split-plot design, which included three production systems (single piatã grass; single hybrid sorghum; mixed cultivation of sorghum and piatã grass). Half-plots consisted of three forage ages at harvest (with 70, 90 and 110 days after seeding). Variables included agronomical characteristics, productivity and nutrition value. Regardless of the evaluated systems, cutting age affected agronomical characteristics and in vitro digestibility of organic matter (IVDOM). Production was highest (4,048 kg ha-1) within the integrated system. Regardless of cutting age, monoculture sorghum had the highest crude protein level. Results showed that integrated sorghum and piatã grasses were an asset for forage productivity. Forages had higher values in crude protein and in in vitro digestibility of organic matter on the 70th day after seeding.